Highly Effective and Noninvasive Near‐Infrared Eradication of a Staphylococcus aureus Biofilm on Implants by a Photoresponsive Coating within 20 Min. Issue 17 (19th July 2019) - Li, Mu; Li, Liqian; Su, Kun; Liu, Xiangmei; Zhang, Tianjin; Liang, Yanqin; Jing, Doudou; Yang, Xianjin; Zheng, Dong; Cui, Zhenduo; Li, Zhaoyang; Zhu, Shengli; et al.
Abstract: Biofilms have been related to the persistence of infections on medical implants, and these cannot be eradicated because of the resistance of biofilm structures. Therefore, a biocompatible phototherapeutic system is developed composed of MoS2, IR780 photosensitizer, and arginine–glycine–aspartic acid–cysteine (RGDC) to safely eradicate biofilms on titanium implants within 20 min. The magnetron‐sputtered MoS2 film possesses excellent photothermal properties, and IR780 can produce reactive oxygen species (ROS) with the irradiation of near‐infrared (NIR, λ = 700–1100 nm) light. Consequently, the combination of photothermal therapy (PTT) and photodynamic therapy (PDT), assisted by glutathione oxidation accelerated by NIR light, can provide synergistic and rapid killing of bacteria, i.e., 98.99 ± 0.42% eradication ratio against a Staphylococcus aureus biofilm in vivo within 20 min, which is much greater than that of PTT or PDT alone. With the assistance of ROS, the permeability of damaged bacterial membranes increases, and the damaged bacterial membranes become more sensitive to heat, thus accelerating the leakage of proteins from the bacteria. In addition, RGDC can provide excellent biosafety and osteoconductivity, which is confirmed by in vivo animal experiments. Abstract : With the assistance of glutathione oxidation, a reactive oxygen species‐enhanced photothermal therapy strategy provides synergistic and rapid eradication of already‐formed biofilms. Moreover, the grafting of arginine–glycine–aspartic acid–cysteine provides excellent biosafety and osteoconductivity of the hybrid coating.